2023
DOI: 10.5194/egusphere-2023-231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stochastic properties of coastal flooding events – Part 1: CNN-based semantic segmentation for water detection

Abstract: Abstract. The frequency and intensity of coastal flooding is expected to accelerate in low-elevation coastal areas due to sea level rise. Coastal flooding due to wave runup affects coastal ecosystems and infrastructure, however it can be difficult to monitor in remote and vulnerable areas. Here we use a camera-based system to monitor wave runup as part of the after-storm recovery of an eroded beach on the Texas coast. We analyze high-temporal resolution images of the beach using Convolutional Neural Network (C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We chose the Deeplab v3+ architecture, which incorporates a Resnet-18 model pretrained on ImageNet, to form the backbone of our CNN analysis for semantic segmentation. Of the 156 high-quality images, we used 132 to train Resnet-18, following previous studies that indicated over 100 images sufficient for reliable semantic segmentation prediction via transfer learning [19].…”
Section: Patchwise Training Of Cnnmentioning
confidence: 99%
“…We chose the Deeplab v3+ architecture, which incorporates a Resnet-18 model pretrained on ImageNet, to form the backbone of our CNN analysis for semantic segmentation. Of the 156 high-quality images, we used 132 to train Resnet-18, following previous studies that indicated over 100 images sufficient for reliable semantic segmentation prediction via transfer learning [19].…”
Section: Patchwise Training Of Cnnmentioning
confidence: 99%